How to code in 10 easy lessons : learn how to design and code your very own computer game - McManus, Sean, 1973- (Super skills (Irvine, Calif.), 2015)
"From writing simple coding instructions using Scratch software, to learning the coding skills to create your own computer game and even design your own website, this book leads the way. By breaking this daunting subject down into the 10 "super skills" needed, young readers can get familiar with computer coding and build on their skills as they progress through the book."--Provided by publisher.